2021
DOI: 10.3390/vaccines9040345
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of DNA-Launched Virus-Like Particle Vaccines in an Immune Competent Mouse Model of Chikungunya Virus Infection

Abstract: Chikungunya virus (CHIKV) infection can result in chronic and debilitating arthralgia affecting humans in tropical and subtropical regions around the world, yet there are no licensed vaccines to prevent infection. DNA launched virus like particle (VLP) vaccines represent a potentially safer alternative to traditional live-attenuated vaccines; however, fully characterized immunocompetent mouse models which appropriately include both male and female animals for preclinical evaluation of these, and other, vaccine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The expressed proteins subsequently form viral particles that are similar to intact virions because of their self-assembly capacity. However, VLPs are replication-incompetent because of the absence of genomic RNA and thus, have a better safety profile compared to LAV [ 211 ].…”
Section: The Current Development Of Vaccine Candidates Against Chikvmentioning
confidence: 99%
“…The expressed proteins subsequently form viral particles that are similar to intact virions because of their self-assembly capacity. However, VLPs are replication-incompetent because of the absence of genomic RNA and thus, have a better safety profile compared to LAV [ 211 ].…”
Section: The Current Development Of Vaccine Candidates Against Chikvmentioning
confidence: 99%
“…One example is Tropis, which is commercially available and has been used to vaccinate over seven million people (mostly children) around the world ( [5] , [6] , [7] , [8] , [9] , PharmaJet personal communication). In general, there have been a number of vaccines evaluated using jet delivery, targeting protection from COVID, polio, rabies, hantaviruses, human papillomavirus (HPV), zika, HIV, chikungunya, dengue, influenza, and measles-mumps-rubella (MMR) [3] , [4] , [6] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] . These vaccines have been composed of mRNA or DNA that encode viral antigens, or attenuated or inactivated viruses [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] .…”
Section: Introductionmentioning
confidence: 99%
“…In general, there have been a number of vaccines evaluated using jet delivery, targeting protection from COVID, polio, rabies, hantaviruses, human papillomavirus (HPV), zika, HIV, chikungunya, dengue, influenza, and measles-mumps-rubella (MMR) [3] , [4] , [6] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] . These vaccines have been composed of mRNA or DNA that encode viral antigens, or attenuated or inactivated viruses [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] . A protamine-complexed mRNA vaccine for rabies was evaluated in a Phase I trial using jet delivery (Tropis (ID) and Stratis (IM)) and was found to be safe and effective when delivered via jet injection but not effective when needle/syringe was used [10] .…”
Section: Introductionmentioning
confidence: 99%